Adsorbents synthesized from dewatered oily sludge and their adsorption of reactive brilliant red X-3B in aqueous solution. Issue 52 (7th November 2016) - Guo, Hao; Lin, Hai; Li, Ying; Li, Xinliang; Feng, Suping; Zhu, Ying
Abstract: Oily sludge was first dewatered using Fenton's reagent and sawdust, and was then made into adsorbents. These lab-made adsorbents were applied to adsorb the reactive brilliant red X-3B dye in liquid phase. The adsorbent was activated at 800°C for 45 min in an inert atmosphere after activation for 24 h by ZnCl2 at 40 wt%. Results show that the adsorbent has a maximum apparent surface area of 183 m 2 g −1 and total volume of 0.19 cm 3 g −1 . The results of the kinetic and isothermal studies show that the adsorbent fits the pseudo-second order and Langmuir models, respectively. Moreover, the adsorption is confirmed to be an endothermal process. The adsorbent achieved a maximum equilibrium adsorption capacity of 67.72 mg g − 1 at 30°C with an equilibrium time of 8 h. A total of 8 metals, including heavy metals, were found in the raw material, and most of them, except for Fe, can hardly be dissolved into the liquid after adsorption. Although the adsorption capacity is lower than that of common commercial-activated carbon, the lab-made adsorbent has the advantages of low cost and low adsorption equilibrium time.